Estimating Acceptability of Financial Health Incentives. (August 2017) - Bigsby, Elisabeth; Seitz, Holli H.; Halpern, Scott D.; Volpp, Kevin; Cappella, Joseph N.
A growing body of evidence suggests that financial incentives can influence health behavior change, but research on the public acceptability of these programs and factors that predict public support have been limited. A representative sample of U.S. adults ( N = 526) were randomly assigned to receive an incentive program description in which the funding source of the program (public or private funding) and targeted health behavior (smoking cessation, weight loss, or colonoscopy) were manipulated. Outcome variables were attitude toward health incentives and allocation of hypothetical funding for incentive programs. Support was highest for privately funded programs. Support for incentives was also higher among ideologically liberal participants than among conservative participants. Demographics and health history differentially predicted attitude and hypothetical funding toward incentives. Incentive programs in the United States are more likely to be acceptable to the public if they are funded by private companies.